Barometer of fear : an insider's account of rogue trading and the greatest banking scandal in history - Stenfors, Alexis (Zed Books, 2017)
"The LIBOR affair has been described as the 'biggest banking scandal in history', a deception affecting not only banks but also corporations, pension funds and ordinary people. But was this just the tip of the iceberg? Was the scandal the work of a few 'bad apples' or an inevitable result of a financial system rotten to its core? Labelled 'one of the world's most infamous rogue traders' in the wake of a mis-marking scandal, Alexis Stenfors went on to rebuild his life and now guides us through the shadowy world of modern banking, providing an insider's account of the secret practices -- including the manipulation of foreign exchange rates -- which have allowed banks to profit from systematic deception. Containing remarkable and often shocking insights derived from his own experiences in the dealing room, as well as his spectacular fall from grace at Merrill Lynch, Barometer of Fear draws back the curtain to a realm that for too long has remained hidden from public view"--Provided by publisher.